Temporal Creatures Tending the Planet: Theology and Biology in Earth Care - Love, Carolyn J. (Zygon, 2025)
God, humans, and environments intertwine, informing humans’ unconscious assumptions about temporality and interconnectedness. This deeply embedded framework often ignores contemporary biological insights about our being-in-the-world and its influences on our experiences of self and creation. This article examines the concept of Earth care through a biological-event understanding that examines genetic inheritance (DNA), epigenetic inheritance, and phenomenology to construct a more robust understanding of human experience and interconnectedness to the environment. The interdisciplinary dialogue between religion, biology, and philosophy aspires to spark the protection of our environment by understanding ourselves as temporal. This article provides an original approach to thinking about the care and keeping of the Earth in a culture that seeks scientific explanations and answers from religion.